This is not a Pipe: Incorporating Art in the Science Curriculum - Jailson Lima; Janis Timm-Bottos (University of Windsor, 2018)
Science courses employ instructional strategies that are based on lecture, drill, and practice to help students memorize collections of facts and procedures of increasing complexity. These strategies emphasize the acquisition of knowledge through the development of logical-mathematical skills employed in problem solving and verbal-linguistic abilities to make sense of the concepts and jargon in the field. Due to its highly abstract character, these science courses deal with complex representations that require an understanding of the role of mental models. Learners need to develop their visual-spatial skills as a means of gradually acquiring visual literacy while grappling with the symbols and conventions displayed in the figures, diagrams, and charts in textbooks. The Art & Science Project started at Vanier College as part of the History of Science course in the liberal arts program and was later adapted for use in three core chemistry courses (General, Solution, and Organic Chemistry) in the science program. The project uses a cross-disciplinary integration between visual arts and the natural sciences to promote a deeper understanding of the role of models. The liberal arts students analyze the parallels between the evolution of modern scientific concepts and the art movements from the same historical periods. Science students create visual representations that portray core ideas and threshold concepts in the field. The goal is to portray these abstractions using visual arts as means of creating meaning through symbolic visual representations while developing new perceptions of visual forms.